Optimization of SIM C Practice Tests as a Requirement for Two-Wheel Driving to Minimize the Rate of Accidents at Pekalongan Police - Tampubolon, Felix (Advances in Police Science Research Journal, 2024)
Accidents are one of the highest causes of mortality in Indonesia. Current conditions, human error dominate the major cause of traffic accidents. Writing this final project aims to identify the causes of accidents and things that need to be done to optimize the SIM C practice test at the Pekalongan Police. This research is qualitative research with a case study approach where data collection is done through interviews, observations, document studies, and focus group discussions (FGD) to a number of sources in the jurisdiction of the Pekalongan Police. the issues raised by researchers using management theory and SWOT analysis theory, as well as several concepts relevant to the problem, namely the concept of optimization, the concept of traffic safety, the concept of safety riding, as well as the concept of a two-wheeled SIM practice test based on Perpol No. 5 of 2021 concerning Issuance and Marking of Driving Permits and Attachments to Perkapolri No. 9 of 2012. The Traffic Unit of the Pekalongan Police is the vanguard of the police in preventing traffic accidents in the jurisdiction of the Pekalongan Police. In addition, the Pekalongan Police Traffic Unit is the primary executor and examiner in carrying out the SIM test, namely, driving ability testing conducted on the public or SIM applicants in theory and practice. Implementation of the SIM C Practice Test at the Pekalongan Polres following the results of an analysis of Management Resources using the POAC Theory, namely Planning, Organizing, Implementation, and Oversight not, as well as analyzing organizational Resources using Management Theory using 4M, namely Man, Money, Material, and Methode. The analysis of Management Resources and Organizational Resources is not following the procedure or SOP in carrying out the SIM practice test, which has been regulated in Perpol No.5 of 2021 concerning the Issuance and Marking of Driving Permits and Attachment to Perkapolri Number 9 of 2012. On the other hand, to optimize the implementation of the SIM C practice test, evaluation, and innovations are needed in efforts to improve the implementation of the SIM C practice test.